Analisis Tindak Pidana Cukai Rokok: Perspektif Hukum Pidana Ekonomi dan Kriminologi - Ahmad Yunus; Moh. Jeweherul Kalamiah; Hasbi Ash Shiddiqi (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
Cigarette excise crimes are a form of economic crime that significantly impact state revenues, national economic stability, and the market balance of the tobacco industry. This phenomenon not only causes material losses to the state but also has implications for social justice and the economic order of society. This study aims to analyze in depth the characteristics, causes, and implications of cigarette excise crimes from the perspective of economic criminal law and criminology. The research method used is a juridical-normative approach combined with criminological analysis to identify the relationship between social, economic, and legal factors in cigarette excise violations. The results indicate that these crimes are driven by economic motives, regulatory imbalances, weak law enforcement, and low public awareness of excise obligations. Through this analysis, the study emphasizes the need for synergy between criminal law policy, economic oversight, and a criminological approach to create an effective and equitable excise control system in Indonesia.